Closed-door lecture by Professor Volker Nienhaus on “Islamic Capital Markets and the Public Interest (Maslahah)”, organised by the Malaysian Securities Commission and the University of Malaya - Yussof, Sheila Ainon (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2011)
In his closed-door lecture at the Malaysian Securities Commission, renowned senior German economist Professor Volker Nienhaus highlighted the problems in using the efficiency model as a point of reference to measure the performance of the Islamic financial industry globally. This was due to critics perceiving it to be too capitalist or conventional.